Analisis Pengelolaan Aset Pemerintah Daerah Kabupaten Bolaang Mongondow - Niu, Fitria Ayu Lestari; Kalangi, Lintje; Lambey, Linda (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. This study aims to analyze the suitability of the implementation the local assets management with regulations, analyze the constraints faced in the management of local assets and efforts made for better management of regional assets. This is a qualitative study with case study approach. Data were obtained through in-depth interview technique, documentation study and observation. The result of this research shows that the local asset management in Bolaang Mongondow is implemented based on Regulation by Minister of Home Affairs No. 19 of 2016 which covers the process of planning needs and budgeting, procurement, use, utilization, security and maintenance, assessment, deletion, alienation, administration and coaching, supervision and control. But the process of destruction has not been conducted. It is because the local government has judged that there is no property belonging to the region being eligible to be destroyed. Additionally, there are obstacles encountered in asset management that are low compliance of regional apparatuses, lack of local regulations for local asset management, ineffective asset inventories, insufficient human resource competencies, lack of firm leadership commitments and resource constraints in the form of budgets and facilities in local assets management. Efforts have been conducted such as asset valuation, legal audit, asset inventory and improvement in leadership commitment. However, these efforts are required to be strongly supported by the regulation in the form of local regulations, improvement in compliance, attitude, perception, and responsibility for regional apparatus, assertiveness by the leadership, need a reward and punishment strategy for the performance of regional apparatus, involving the steward in the planning process and the use of SIMDA-BMD for the administration process in each regional work unit.Keywords: Local Asset Management, Compliance, Human Resources, Asset InventoriesAbstrak. Penelitian ini bertujuan untuk menganalisis kesesuaian pelaksanaan pengelolaan aset daerah dengan regulasi, menganalisis kendala yang dihadapi serta upaya yang dilakukan untuk memperbaiki pengelolaan aset daerah yang lebih baik. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui teknik wawancara yang mendalam, studi dokumentasi dan observasi. Hasil penelitian menunjukkan bahwa pengelolaan aset daerah Kabupaten Bolaang Mongondow dilaksanakan berdasarkan Permendagri No. 19 Tahun 2016 yang meliputi proses perencanaan kebutuhan dan penganggaran, pengadaan, penggunaan, pemanfaatan, pengamanan dan pemeliharaan, penilaian, penghapusan, pemindahtanganan, penatausahaan serta pembinaan, pengawasan dan pengendalian. Namun proses pemusnahan belum dilakukan karena pemerintah daerah menilai bahwa belum ada barang milik daerah yang memenuhi syarat untuk dimusnahkan. Kendala yang ditemui dalam pengelolaan aset yaitu rendahnya kepatuhan aparatur daerah, belum adanya peraturan daerah yang mengatur proses pengelolaan aset daerah, inventarisasi aset yang belum efektif, kompetensi sumber daya manusia yang belum memadai, lemahnya komitmen pimpinan serta kurangnya sumber daya dalam bentuk anggaran dan fasilitas dalam pengelolaan aset daerah. Upaya yang dilakukan yaitu mengadakan penilaian aset, legal audit, inventarisasi aset dan perbaikan dalam komitmen pimpinan. Namun upaya ini masih perlu didukung dengan adanya regulasi dalam bentuk peraturan daerah, perbaikan dalam hal kepatuhan, sikap, persepsi, dan tanggung jawab aparatur daerah, ketegasan pimpinan, adanya strategi reward dan punishment atas kinerja aparatur daerah, melibatkan pengurus barang dalam proses perencanaan serta penggunaan SIMDA-BMD untuk proses penatausahaan pada masing-masing SKPD.Kata Kunci: Pengelolaan Aset Daerah, Kepatuhan, Sumber Daya Manusia, Inventarisasi Aset.Â